Born Digital, Die Digital. Potentials and Risks of Digital Archives - Roberta Angari (Pad, 2023)
The contribution deals with the theme of preservation and access to knowledge, with particular attention to the approaches and methodologies employed in the design of digital platforms useful for preserving culture and memory, guaranteeing access for future generations. An analysis of the relevant scientific literature and state of the art shows how, especially in the face of the pandemic emergency, experiences have been consolidated and centered on the design of platforms, such as digital archives, which, while preserving culture and memory, also make them accessible, regardless of the possibility of access to physical structures. The change generated by the digital has redefined the relationship between society and culture, and between people and memory and has led to the need to think about how people access to memory and cultural heritage, in particular to a new category of artifacts, the born-digital ones, which risk dispersion and deterioration due to technological obsolescence. The contribution, therefore, addresses these issues to identify, through context analysis, a methodology useful for the creation of a digital archive, attempting to overcome those limits dictated by self-referential systems, which do not guarantee democratization and access to culture for a non-specialist audience.